2011
DOI: 10.1103/physrevlett.107.166602
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Fermi Liquid in Epitaxial Graphene from Quantum Transport Measurements

Abstract: We have performed magnetotransport measurements on monolayer epitaxial graphene and analyzed them in the framework of the disordered Fermi liquid theory. We have separated the electron-electron and weak-localization contributions to resistivity and demonstrated the phase coherence over a micrometer length scale, setting the limit of at least 50 ps on the spin relaxation time in this material.Funding Agencies|Swedish Research Council||Foundation for Strategic Research||UK National Measurement Office||EU|

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
86
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 23 publications
12
86
2
Order By: Relevance
“…For the elastic intervalley scattering term L i , we find a weak trend with carrier density with a negative exponent of −0.173. Previous temperature 9,11 and backgate studies 11 found no strong variation of L i with either temperature or carrier density. Given that L i is due to short range, atomically sharp scatterers and device-edge scattering, it would be expected to be highly dependent on the device characteristics.…”
Section: Scattering Lengthsmentioning
confidence: 99%
See 4 more Smart Citations
“…For the elastic intervalley scattering term L i , we find a weak trend with carrier density with a negative exponent of −0.173. Previous temperature 9,11 and backgate studies 11 found no strong variation of L i with either temperature or carrier density. Given that L i is due to short range, atomically sharp scatterers and device-edge scattering, it would be expected to be highly dependent on the device characteristics.…”
Section: Scattering Lengthsmentioning
confidence: 99%
“…These terms do have a carrier density dependence, however, the fitting parameters were found to vary with carrier density. Lara-Avila et al 9 use an alternative model and find their data to be well modeled by the addition of a electron spin-flip scattering term. This is due to scattering from the localized magnetic moment of spin-carrying defects which is likely to be dependent on the sample preparation method and could mask or dominate underlying trends in the dependence of the phase coherence length on carrier density.…”
Section: Scattering Lengthsmentioning
confidence: 99%
See 3 more Smart Citations